Journals accepting case reports - Terri Gotschall; Angela Spencer; Margaret A. Hoogland; Elisa Cortez; Elizabeth Irish (Journal of the Medical Library Association, 2023)
Background: Few resources exist to support finding journals that accept case reports by specialty. In 2016, Katherine Akers compiled a list of 160 journals that accepted case reports, which many librarians continue to use 7 years later. Because journals’ editorial policies and submission guidelines evolve, finding publication venues for case reports poses a dynamic problem, consisting of reviewing a journal’s author guidelines to determine if the journal accepts case report manuscripts. This project aimed to create a more up to date and extensive list of journals that currently accept case reports.